The Effectiveness 3D Models Online Modules to Practice Mastery of Solar System Conceptual Knowledge - Dhanang Setyo Ervana; Raharjo Raharjo; Munasir Munasir (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This study aims to describe the effectiveness of 3D models online modules to practice mastery of solar system conceptual knowledge. The effectiveness of the 3D models online modules was measured using a conceptual knowledge mastery test instrument which was tested on 15 7th grade junior high school students in Jombang district, East Jawa, Indonesia. The test instrument consisted of 30 questions with the addition of the Certainty of Response Index (CRI) which was divided into 3 meetings and each meeting tested 10 questions. The results showed that 48.67% of students had been able to master conceptual knowledge when given the 3D models online modules. However, 31.11% of students experienced misconceptions, 8.44% answered correctly because of luck and 11.78% had not been able to master conceptual knowledge. Because the resulting misconceptions fall into the moderate criteria, it can be concluded that the 3D models online modules in general has not been effective in practicing mastery of solar system conceptual knowledge. When examined further, this ineffectiveness is found in the cognitive dimensions of C4, learning indicators (LI) 1, 3 and 4, as well as conceptual knowledge sub-types (CKST) 1 and 3. While the effective 3D models online modules in cognitive dimensions C2 and C5, learning indicators (LI) 2 and 5, and conceptual knowledge sub-types (CKST) 2